Formation of a traditional Chinese medicine self-assembly nanostrategy and its application in cancer: a promising treatment - Ju Huang; Yu Zhu; Hang Xiao; Jingwen Liu; Songtao Li; Qiao Zheng; Jianyuan Tang; Xiangrui Meng (BMC, 2023)
Abstract Traditional Chinese medicine (TCM) has been used for centuries to prevent and treat a variety of illnesses, and its popularity is increasing worldwide. However, the clinical applications of natural active components in TCM are hindered by the poor solubility and low bioavailability of these compounds. To address these issues, Chinese medicine self-assembly nanostrategy (CSAN) is being developed. Many active components of TCM possess self-assembly properties, allowing them to form nanoparticles (NPs) through various noncovalent forces. Self-assembled NPs (SANs) are also present in TCM decoctions, and they are closely linked to the therapeutic effects of these remedies. SAN is gaining popularity in the nano research field due to its simplicity, eco-friendliness, and enhanced biodegradability and biocompatibility compared to traditional nano preparation methods. The self-assembly of active ingredients from TCM that exhibit antitumour effects or are combined with other antitumour drugs has generated considerable interest in the field of cancer therapeutics. This paper provides a review of the principles and forms of CSAN, as well as an overview of recent reports on TCM that can be used for self-assembly. Additionally, the application of CSAN in various cancer diseases is summarized, and finally, a concluding summary and thoughts are proposed. We strongly believe that CSAN has the potential to offer fresh strategies and perspectives for the modernization of TCM.